From Blood to Data: An Ethnographic Account of the Construction of the Generation Scotland Population Genetic Database - Marsden, Wendy (My University, 2008)
This thesis is an examination of a population genetic database as both a social and scientific entity. Science and social science usually operate in a dichotomy this is a synergy of the two. The thesis examines practices and processes, and reveals how the formation of the Generation Scotland assemblage is the producer of multiple disconnections and connections layered in the science, technology, objects, people and places. The story is based on a multi‐sited ethnography that moves from the medical setting of blood sample and data collection, through the practices and processes of the laboratory, to end up in the much more diffuse settings of computer analysis. The blood sample is transformed into digital genetic data, and then connected to diverse other data for research. It traces the transformation and aggregation of heterogeneous elements which will become fixed in the population genetic database through scientific ordering and relationships which will be rendered immutable by the technology. In the processes described here, people’s bodies, and information about them, are explicitly rendered as research ‘resources’. The thesis contributes to the growing knowledge of population genetic databases, and it is a response to calls from social science to understand better the science and technology that are currently changing the shape of the social world. Disconnections and connections are creating a framework of new referents between health and illness, identity and relationships in a way that rearticulates the body and the population.
Keywords: Law; Genetic data